PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS MULTIMEDIA TIGA DIMENSI BERCODE UNTUK SEKOLAH DASAR - Triayomi, Ria (Jurnal Inovasi Pendidikan, 2019)
This study aims to produce a three dimensional encoded multimedia learning media for primary schools that are valid, practical and effective towards learning outcomes. The subjects of the study were students of grade VI of elementary school. This learning media is developed through three stages namely requirements analysis, design, development and implementation stages. To see the validity of the practicality expert evaluation is used one-on-one evaluation and small group evaluation, while to see the effectiveness used field tests. The results showed an expert evaluation of 4.34 with very valid criteria. One to one results are suggestions and comments. The results of the small group show an average of 3.8 or 76% means the response of students is positive. Learning outcomes obtained an average of 85.86. By using expert evaluations, one-on-one evaluations, small group evaluations, and field tests, it was concluded that the three-dimensional coded multimedia learning media for elementary schools that were developed were valid, practical, and had effectiveness in learning outcomes.